2015
DOI: 10.1007/s13592-015-0356-z
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of managed honey bee 2013–2014 annual colony losses in the USA

Abstract: -Honey bee colony losses are a major concern in the USA and across the globe. Long-term data on losses are critical for putting yearly losses in context. for the whole year. While total winter loss was one of the lowest reported in 8 years, 66 % of all beekeepers had higher losses than they deemed acceptable.honey bee / survey / mortality / colony losses / USA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
175
2
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(198 citation statements)
references
References 40 publications
5
175
2
16
Order By: Relevance
“…Similar values of colony losses were reported in other parts of the world. For example, in the USA, vanEngelsdorp et al (2008 reported colony losses for fall/winter -2008to be 31 % and 36 %, respectively (vanEngelsdorp et al 2008 Lee et al (2015) reported colony losses in the USA to be 19.8 % during the summer, 23.7 % during the winter, and 34.1 % for the whole year. Average losses were 15.1 % during the summer, 44.8 % during the winter, and 51.1 % for the whole year.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…Similar values of colony losses were reported in other parts of the world. For example, in the USA, vanEngelsdorp et al (2008 reported colony losses for fall/winter -2008to be 31 % and 36 %, respectively (vanEngelsdorp et al 2008 Lee et al (2015) reported colony losses in the USA to be 19.8 % during the summer, 23.7 % during the winter, and 34.1 % for the whole year. Average losses were 15.1 % during the summer, 44.8 % during the winter, and 51.1 % for the whole year.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…Honey bees are a non-target organism that frequently encounters pesticides especially when colonies are located in and around agroecosystems (Mullin et al 2010). Exposure to sublethal levels of pesticides might be contributing to colony losses (Dively et al 2015) that can average 30 % or more each year (Lee et al 2015b). Preventing colony losses from encounters with pesticides requires more judicious and careful use of these chemicals, and a greater understanding of the harm they might pose.…”
Section: Introductionmentioning
confidence: 99%
“…Reliance on insects for pollination services is growing even as populations of native and managed pollinators exhibit concurrent declines (4,5). For example, in 2013−2014, total US honey bee colony losses were 34%, but beekeepers on average lost 51% of their colonies (6). Declines in managed honey bees and native bees put significant pressure on global food supplies, plant-pollinator networks, agricultural producers, and ecosystem function (7,8).…”
mentioning
confidence: 99%